Modernisasi Hukum Perkawinan Islam di Indonesia: Respons Ulama Atas Rancangan Ordonansi Perkawinan Era Hindia-Belanda - Arif, Miftakhul (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
The colonial government's marriage regulations sparked debates among Islamic scholars, with responses ranging from acceptance and rejection to compromise. This study examines the ulama's response to the draft Marriage Ordinance in the Dutch East Indies, as reported in the Suara Nahdlatul Ulama magazine in 1927. As library-based research, this empirical study on Islamic law employs a socio-historical and legal-political approach. Data were collected from historical documents, including the 1927 edition of Suara Nahdlatul Ulama and other relevant literature. The study found that ulama’s responses to the draft Marriage Ordinance in the Dutch East Indies fell into three categories: rejection, acceptance, and compromise. From a legal-political perspective, these responses reflect the dynamics between Islamic and colonial law. Rejection symbolized efforts to maintain Islamic legal autonomy, acceptance was seen as a step toward modernizing Islamic marriage law, while compromise indicated negotiations between the two systems. The findings contribute to the discourse on the interaction between Islamic and colonial law in Indonesia.